Insight Into Polysaccharides From Panax ginseng C. A. Meyer in Improving Intestinal Inflammation: Modulating Intestinal Microbiota and Autophagy - Wang, Dandan; Shao, Shuai; Zhang, Yanqiu; Zhao, Daqing; Wang, Mingxing (Frontiers in Immunology, 2021)
Polysaccharides from Panax ginseng C. A. Meyer (P. ginseng) are the main active component of P. ginseng and exhibit significant intestinal anti-inflammatory activity. However, the therapeutic mechanism of the ginseng polysaccharide is unclear, and this hinders the application for medicine or functional food. In this study, a polysaccharide was isolated from P. ginseng (GP). The primary structure and morphology of the GP were studied by HPLC, FT-IR spectroscopy, and scanning electron microscopy (SEM). Further, its intestinal anti-inflammatory activity and its mechanism of function were evaluated in experimental systems using DSS-induced rats, fecal microbiota transplantation (FMT), and LPS-stimulated HT-29 cells. Results showed that GP modulated the structure of gut microbiota and restored mTOR-dependent autophagic dysfunction. Consequently, active autophagy suppressed inflammation through the inhibition of NF-κB, oxidative stress, and the release of cytokines. Therefore, our research provides a rationale for future investigations into the relationship between microbiota and autophagy and revealed the therapeutic potential of GP for inflammatory bowel disease.